SWOT analysis of the models used by social enterprises in scaling effective refractive error coverage to achieve the 2030 in SIGHT in Kenya - Shadrack Muma; Kovin Shunmugam Naidoo; Rekha Hansraj (Scientific Reports, 2024)
Abstract Uncorrected refractive error has predominantly been delivered through commercial entrepreneurship in Kenya. However, to achieve the 2030 IN SIGHT, integration of other forms of entrepreneurship such as the social entrepreneurship is desirable to supplement the efforts of the dominant commercial entrepreneurship. Therefore, this study intended to undertake a SWOT analysis of the current models used by social enterprises in scaling effective refractive error coverage to achieve the 2030 IN SIGHT in Kenya. A review of the seven national strategic plans for eye health in Kenya was undertaken to get a glimpse on the efforts directed towards uncorrected refractive error in achieving the 2030 IN SIGHT. The review was inclined towards assessing the efforts directed by the strategic plans towards scaling human resource, spectacle provision and refraction points. A SWOT analysis was undertaken based on the financial, impact and the approach report for each model. A key informant interview was conducted with a representative and three to five members of the social enterprise about the model. Thereafter, the modified SWOT analysis based on the review and the interview was presented to the representatives of the social enterprises. Purposive sampling was used to identify seven models used by social enterprises in the delivery of refractive error services in Kenya. Finally, the recommendations were presented to key opinion leaders for an input through a Delphi technique. Out of the seven national strategic plans for eye health reviewed, only the strategic plan 2020–2025 intends to establish optical units within 15 different counties in Kenya. Of the seven models currently utilized by social enterprises, only the Kenya Society for the Blind has integrated the telemedicine concept. On application of mHealth, all of the social enterprises models tend to embrace the approach for screening activities. None of the models has a strengthened referral pathway utilizing telereferral and telemedicine. Out of all the models, only Operation Eyesight Universal, Fred Hollow Foundation and Peek Acuity do not depend on sales of subsidized spectacles for sustainability. Every model has the capacity to propel the delivery of refractive error services depending on its comprehensiveness. However, for the 2030 IN SIGHT to be achieved, models prioritizing human resource through telemedicine integration, service provision across all sectors, awareness creation and enhancing cost efficiency are desirable.